Realizing the opportunities for sustainable landscape management in Central Rift Valley, Ethiopia - Mekuria, Wolde; Haile, Alemseged Tamiru; Moges, A.; Girma, R.; Teshale, T.; Yakob, Getahun (International Water Management Institute, 2024)
In Ethiopia, forest landscapes and freshwater ecosystems are important for biodiversity conservation, providing a range of benefits and services that are fundamental to the environment, society and economy. However, human activities such as agricultural expansion, land-use and land-cover changes, together with climate change have impacted these ecosystems and the services they provide. Despite these challenges, 4 years of field studies (2019-2023) of the SaWeL (Safeguarding Sahelian Wetlands for Food Security) project in the western catchment of Lake Ziway, one of the freshwater ecosystems in Ethiopia, demonstrates various opportunities that exist to better manage the forest landscapes and freshwater ecosystems. This brief provides recommendations on how to improve the planning, design and implementation of landscape management practices, and how to use the Ecologically Sustainable Agricultural Water Management (ESAWM) framework. The brief is also intended to help local-level practitioners (government, Nongovernmental organizations [NGOs], and private sectors) realize existing opportunities for sustainable landscape management.